2020
DOI: 10.2147/ijn.s280976
|View full text |Cite
|
Sign up to set email alerts
|

<p>Silver-Based Nanomaterials as Therapeutic Agents Against Coronaviruses: A Review</p>

Abstract: Since the identification of the first human coronavirus in the 1960s, a total of six coronaviruses that are known to affect humans have been identified: 229E, OC43, severe acute respiratory syndrome coronavirus (SARS-CoV), NL63, HKU1, and Middle East respiratory syndrome coronavirus (MERS-CoV). Presently, the human world is affected by a novel version of the coronavirus family known as SARS-CoV-2, which has an extremely high contagion rate. Although the infection fatality rate (IFR) of this rapidly spreading v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 116 publications
0
37
0
Order By: Relevance
“…Among the different types of metallic NPs, the antiviral activity of silver NPs (AgNPs) on SARS‐CoV‐2 is of particular interest (Argentiere, Cella, Cesaria, Milani, & Lenardi, 2016; Das et al, 2020; Durán, Silveira, Durán, & Martinez, 2015; Hossain, 2020; Teirumnieks, Balchev, Ghalot, & Lazov, 2021). AgNPs are known for their high antimicrobial activity, biocompatibility, and low toxicity in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different types of metallic NPs, the antiviral activity of silver NPs (AgNPs) on SARS‐CoV‐2 is of particular interest (Argentiere, Cella, Cesaria, Milani, & Lenardi, 2016; Das et al, 2020; Durán, Silveira, Durán, & Martinez, 2015; Hossain, 2020; Teirumnieks, Balchev, Ghalot, & Lazov, 2021). AgNPs are known for their high antimicrobial activity, biocompatibility, and low toxicity in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…In all of them, there are four types of proteins called spike (S), envelope (E), membrane (M), and nucleocapsid (N) [5]. Only protein S can bind to the receptors [6,7] Although reports indicate that SARS-CoV-2 is more than 80% similar to the SARS genome and 50% similar to MERS, unfortunately, the SARS-CoV-2 transmission rate is much higher, but the resulting mortality rate is lower. Also, unlike SARS-CoV and MERS-CoV, which are more common in the hospital environment, SARS-CoV-2 is more prevalent in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Today, nanoparticles have entered the field of corona control as an important issue [15], especially since the virus has a diameter of 60 to 140 nm, which is only slightly larger than nanoparticles, and this similarity in diameter is very beneficial [6]. The small size of the nanoparticles helps them to enter [1].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the effectiveness of AgNMs as an antiviral agent has been verified in humans against many viruses, including human immunodeficiency virus, hepatitis B virus, herpes simplex virus, respiratory syncytial virus, poliovirus, adenovirus, and monkeypox virus [ 20 ]. Recently, Das et al independently of our group reviewed the possibility of AgNMs as therapeutic agents against coronavirus and ultimately they suggested applying nanomaterials coating in personal protection equipment for the prevention of infection-associated coronaviruses [ 23 ]. In the same case, Carvalho et al reported the most common NMs with anti‐coronavirus activity against animal and human COVs (Fig.…”
Section: Introductionmentioning
confidence: 99%